Legal Policy as a Multi-Aspective Concept: General Theoretical Aspect - Vladimir Valentinovich Kozhevnikov (Polit Journal Scientific Journal of Politics, 2024)
This scientific article analyzes the concept of legal policy, as well as various aspects of the concept of “legal policy”. Noting that the subject of legal policy is the state, its functions in the political sphere are determined. Attention is drawn to the content of some principles of legal policy.